Protecting Digital Intellectual Property Rights:A Literature Review - Hombal, S. G.; Prasad, K. N. (Journal of Information and Knowledge, 2011)
This article is a review of literature on Digital Intellectual Property Rights, the application of information and communication technology for providing information and rights, the role played by the professional librarians in protecting digital intellectual property rights while rendering information services to a much wider user community.